2016
DOI: 10.1016/j.apsusc.2016.03.138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the thermal decomposition processes of several aminoalcohol-based ZnO inks with one containing ethanolamine

Abstract: Four inks for the production of ZnO semiconducting films have been prepared with zinc acetate dihydrate as precursor salt and one among the following aminoalcohols: aminopropanol (APr), aminomethyl butanol (AMB), aminophenol (APh) and aminobenzyl alcohol (AB) as stabilizing agent. Their thermal decomposition process has been analyzed in situ by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and evolved gas analysis (EGA), whereas the solid product has been analysed ex-situ by X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Next reaction with -OH would give lactams or lactims.As a complementary experiment, Evolved Gas Analysis was used to elucidate the composition of the samples before and after degradation under illumination in air. A variety of mass fragments from m/z = 12 to 86 was detected from the inks, and their respective EGA curves were classified according to their dependence on temperature24,38 . In particular, the group related with m/z = 76 (Figure 5a) can be associated with some non-bonded and degraded EA decomposition fragments 39 .…”
mentioning
confidence: 99%
“…Next reaction with -OH would give lactams or lactims.As a complementary experiment, Evolved Gas Analysis was used to elucidate the composition of the samples before and after degradation under illumination in air. A variety of mass fragments from m/z = 12 to 86 was detected from the inks, and their respective EGA curves were classified according to their dependence on temperature24,38 . In particular, the group related with m/z = 76 (Figure 5a) can be associated with some non-bonded and degraded EA decomposition fragments 39 .…”
mentioning
confidence: 99%
“…When several volatiles evolve simultaneously, the intensity of some fragments results from the contribution of different volatiles rendering their identification difficult. To simplify the analysis, we have proceeded, as in our previous study on several aminoalcohols, [4] and considered that the fragments arising from a single volatile will follow the same temperature dependence. Consequently, the fragments have been classified according to their intensity dependence on temperature (details are given in Figure S1A–E) and one representative fragment of each group has been plotted in Figure S1F.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO-based nanomaterials are crucial in various areas, including biological, optical, photocatalysis, and so forth [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. In general, these nanomaterials are prepared using a zinc(II) salt (usually acetate) and an additional organic ligand to stabilize the precursor [3,4,5,6]. It has also been proven that the purity, morphology and properties of these ZnO nanomaterials depend on several factors (i.e., additional reactants, solvents, temperature, experimental conditions etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a good understanding of the molecular structures of the solutes would benefit further development of precursor inks for photovoltaic applications. Thermogravimetric analysis (TGA) of inks containing ethanolamine complexes of various metals carried out by Vila 34 revealed that the majority of the ethanolamine evaporated by B200 1C. In our previous reports, 30,31 spray deposition of inks based on ethanolamine or water onto a hotplate had been attempted, but this technique had proven difficult due to the high viscosity of the solutions.…”
Section: Introductionmentioning
confidence: 99%